2007
DOI: 10.1097/ico.0b013e318033b3d4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conjunctival Autograft With Amniotic Membrane Transplantation for Pterygium Surgery

Abstract: Although better results in the final appearance were achieved using conjunctival autografting than with AMT, AMT can be a useful alternative in pterygium surgery, especially in those patients who may have a limited amount of conjunctiva for future surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 35 publications
2
31
0
2
Order By: Relevance
“…However, Dadeya et al [11 ]did not find any significant difference in recurrence outcome with rotated autografts. Furthermore, as for the use of amniotic membrane as an alternative to CAGs, Küçükerdönmez et al [12] did not yield any significant difference in recurrence rates in a prospective randomized clinical trial of 78 patients, and both Tananuvat and Martin [13 ]and Liang et al [14] demonstrated lower recurrent rates while using CAGs. With CAGs including the limbal areas, Han et al [15] and Torres et al [16] reported recurrence rates of 1.9 and 7.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dadeya et al [11 ]did not find any significant difference in recurrence outcome with rotated autografts. Furthermore, as for the use of amniotic membrane as an alternative to CAGs, Küçükerdönmez et al [12] did not yield any significant difference in recurrence rates in a prospective randomized clinical trial of 78 patients, and both Tananuvat and Martin [13 ]and Liang et al [14] demonstrated lower recurrent rates while using CAGs. With CAGs including the limbal areas, Han et al [15] and Torres et al [16] reported recurrence rates of 1.9 and 7.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, limbal autografts can restore the barrier function against conjunctival invasion to the cornea by facilitating healthy epithelialization as well as by reconstructing the limbal structure [17,19,22,23]. Clinically, many studies have previously demonstrated a significantly lower recurrence rate after limbal-conjunctival autograft surgery than after other procedures, including AM transplantation, MMC application, and the bare-sclera method [1,4,6,11,17]. Limbal-conjunctival grafting was also demonstrated to be superior to conventional conjunctival grafting in lowering the recurrence rate in advanced and recurrent pterygia [11].…”
Section: Discussionmentioning
confidence: 99%
“…This condition causes cosmetic problems and occasional visual disturbance, and successful surgical treatment continues to be a challenge due to a high recurrence rate, especially in patients treated with the bare-sclera technique [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been associated with low complications and recurrence rates, as well as with improved post-operative comfort and favorable cosmetic results. [789]…”
mentioning
confidence: 99%